Administrative Dynamics of Land Distribution in the Age of Empires: Analysis of Sêrat Wadu Aji Collection of the Staatsbibliothek zu Berlin - Ardiana Rahma Dewi (Javanologi: International Journal of Javanese Studies, 2024)
This research is descriptive qualitative, namely research that uses a descriptive qualitative approach. The type of research used is library research or literature and comparative study. The data sources of this research are the manuscript of Sêrat Wadu Aji collection of Staatsbibliothek zu Berlin with catalog number Hs.Or.4374. The data in this research is the text of Sêrat Wadu Aji (Hs.Or.4374) and the content contained in Sêrat Wadu Aji.The conclusion of this research is the manuscript of Sêrat Wadu Aji discusses the history of the Javanese organization from the reign of the Kediri Kingdom to the Surakarta Palace in the field of land administration and explains the duties of abdi dalem.